2020
DOI: 10.1140/epjd/e2020-10111-y
|View full text |Cite
|
Sign up to set email alerts
|

Atomic hydrogen interactions with small polycyclic aromatic hydrocarbons cations

Abstract: When exposed to a thermal beam of hydrogen atoms, gas-phase coronene cations C24H12+ can be sequentially hydrogenated. This process is accompanied by a gradual transition of the electronic structure from aromatic to aliphatic. The planar very stable coronene structure transforms into the significantly weaker corrugated structure, typical for aliphatic molecules. In this study, we have investigated the hydrogenation of 5 smaller polycyclic aromatic hydrocarbon cations using a combination of radiofrequency ion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Meanwhile, there are no clear mass peaks that can attribute to the PAH fragments (loss of C 2 H 2 ) in our obtained mass spectra. We suppose that the non-appearance of fragmentation mainly attributes to the superior stability of large PAH (e.g., HBC) upon hydrogenation compared to smaller PAH (e.g., pyrene, C 16 H 10; Schlathölter et al 2020). And due to that, the large PAHs may play an important role as an ideal catalyst for hydrogen formation in the ISM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, there are no clear mass peaks that can attribute to the PAH fragments (loss of C 2 H 2 ) in our obtained mass spectra. We suppose that the non-appearance of fragmentation mainly attributes to the superior stability of large PAH (e.g., HBC) upon hydrogenation compared to smaller PAH (e.g., pyrene, C 16 H 10; Schlathölter et al 2020). And due to that, the large PAHs may play an important role as an ideal catalyst for hydrogen formation in the ISM.…”
Section: Resultsmentioning
confidence: 99%
“…as typical examples to theoretically study deuteration or hydrogenation and hydrogen/deuterium exchange processes on cationic PAHs. Based on the molecular structural symmetry of HBC + , H/D attachment and abstraction tend to occur on the outer carbon sites according to previous experimental and theoretical investigations (Rauls & Hornekaer 2008;Elias et al 2009;Cazaux et al 2016;Schlathölter et al 2020). As a result, we label the available outer carbon sites as 1−5 in Figure 1 (2 and 5 as well as 3 and 4 are equal).…”
Section: Quantum Calculation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While not definitively identified in space, laboratory (Wagner et al 2000;Sandford et al 2013) and computational (Pauzat & Ellinger 2001;Mackie et al 2018) studies have suggested that HPAHs may contribute to the so-called Aromatic Infrared Bands (Tielens 2008) at wavelengths between 3.4-3.6 µm. Highly hydrogenated PAHs have been shown to be readily formed under a variety of circumstances (Thrower et al 2012;Boschman et al 2012;Klaerke et al 2013;Thrower et al 2014;Cazaux et al 2016;Cruz-Diaz et al 2020;Schlathölter et al 2020), and efficient photo-induced H 2 formation from HPAHs has been demonstrated (Vala et al 2009;Szczepanski et al 2010;Fu et al 2011;Foley et al 2018).…”
Section: Introductionmentioning
confidence: 99%